2015
DOI: 10.1097/ico.0000000000000320
|View full text |Cite|
|
Sign up to set email alerts
|

Corneal Microstructural Changes in Nerve Fiber, Endothelial and Epithelial Density After Cataract Surgery in Patients With Diabetes Mellitus

Abstract: Subbasal nerve density is reduced after cataract surgery in patients with and without DM. However, lower initial SBN density in patients with DM may predispose them to develop diabetic keratopathy. DM does not predispose to greater endothelial loss following phacoemulsification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 34 publications
7
41
0
1
Order By: Relevance
“…Diabetes has been shown in some studies to increase corneal endothelial cell loss with or without intraocular surgery, suggesting that diabetic hyperglycemia contributes to cell death, [7][8][9][10]19 while other studies have found no difference in endothelial cell density with or without intraocular surgery between diabetics and nondiabetics. 63 The same tension has been demonstrated surrounding keratoplasty, where some studies have shown a deleterious impact of diabetes on donor tissue 36 but not outcomes 33,64 using diabetic tissue, and other studies have shown negative impact 32,65 or no impact 33 on keratoplasty outcomes in diabetic recipients. Considering the increasing prevalence of this disease, 66 it is imperative to obtain greater clarity on the issue of diabetes and endothelial cell health.…”
Section: Discussionmentioning
confidence: 84%
“…Diabetes has been shown in some studies to increase corneal endothelial cell loss with or without intraocular surgery, suggesting that diabetic hyperglycemia contributes to cell death, [7][8][9][10]19 while other studies have found no difference in endothelial cell density with or without intraocular surgery between diabetics and nondiabetics. 63 The same tension has been demonstrated surrounding keratoplasty, where some studies have shown a deleterious impact of diabetes on donor tissue 36 but not outcomes 33,64 using diabetic tissue, and other studies have shown negative impact 32,65 or no impact 33 on keratoplasty outcomes in diabetic recipients. Considering the increasing prevalence of this disease, 66 it is imperative to obtain greater clarity on the issue of diabetes and endothelial cell health.…”
Section: Discussionmentioning
confidence: 84%
“…105, 106, 107, 108, 109, 110, 111, 112 The biggest study of the 5, conducted in Vellor, India, involved 153 participants with DM and 163 age-matched controls, and was performed on patients before and after cataract surgery up to 3 months postoperatively. 112 Preoperative examinations showed no statistically significant difference between the groups in any of the corneal endothelial parameters.…”
Section: Cornea Endothelial Diseasementioning
confidence: 99%
“…One of the most common co morbidities among people with cataract is diabetes mellitus [7] , [8] , [9] . We know that increased blood sugar levels affect ocular cells in many ways [10] , [11] and in particular there are reports about the correlation of diabetes and corneal endothelial function [12] , [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%